Analysis of Factors Affecting Behavioral Intention and Use of Behavioral of Mobile Banking Using Unified Theory of Acceptance and Use of Technology 2 Model Approach - Iskandar, Maja; Hartoyo, Hartoyo; Hermadi, Irman (International Review of Management and Marketing, 2020)
The percentage of mobile banking users is currently lower than the number of active internet users with smartphones in Indonesia. The current study extends the Unified Theory of Acceptance and Use of Technology2 (UTAUT2) by adding two important factors, perceived risk and observability. The purpose of this study is to investigate the factors influencing behavioural intention and use behaviour of Mobile banking by customers of Indonesian. Data was collected by conducting an online survey questionnaire completed by 360 respondents. The authors analysed the model through structural equation modelling LISREL. The results showed observability, performance expectation, hedonic motivation, facilitating conditions, habit as positive and significant of behaviour intentions. The perceived risk, and price value indicated negative and significant in explaining behaviour intention. Behavioral intention and experience has positive and significant to use behavior mobile banking Keywords: Behavioral Intention, Mobile Banking, Observability, Perceived Risk, SEM, Unified Theory of Acceptance and Use of Technology 2 JEL Classifications: C31, G02, G21 DOI: https://doi.org/10.32479/irmm.9292